2008
DOI: 10.1021/es800625d
|View full text |Cite
|
Sign up to set email alerts
|

Can Physicochemical and Microbial Soil Properties Explain Enantiomeric Shifts of Chiral Organochlorines?

Abstract: Enantiomeric fractions (EF) of PCB 95, 132, 149, and 174, alpha-HCH, o,p'-DDD, and o,p'-DDT were analyzed in 112 soil samples using two-dimensional gas chromatography and triple-quadrupole mass spectrometry. To assess the soil conditions that facilitate enantioselective fractionation of chiral compounds, EF values of selected PCBs were further correlated with a wide range of physicochemical and microbial soil parameters in an attempt to identify the influential factors and their mutual relations. It was eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
(58 reference statements)
7
29
0
Order By: Relevance
“…This finding is consistent with previous observation that nonracemic EFs appeared to be increasingly probable in soil with relatively low PCB concentrations. 40 Nevertheless, a more likely explanation is that the EFs in the literature were mostly from developed countries where previously used PCBs have stayed in the soil for decades, while a significant proportion of the PCBs in the soils in the present study was newly released. The concentration alone may have a small influence on the degree of enantioselective degradation of PCBs in soil.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This finding is consistent with previous observation that nonracemic EFs appeared to be increasingly probable in soil with relatively low PCB concentrations. 40 Nevertheless, a more likely explanation is that the EFs in the literature were mostly from developed countries where previously used PCBs have stayed in the soil for decades, while a significant proportion of the PCBs in the soils in the present study was newly released. The concentration alone may have a small influence on the degree of enantioselective degradation of PCBs in soil.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…Field blanks [PUF plugs and glass fiber filters (GFFs)] were prepared, and procedural blanks were run with each bath of the field samples to assess blank levels. Several PCBs (PCB 11,26,33,37,40,71,76,103,111,128,170,175,190, and 209) were found in the procedural and field blanks; however, their quantities were less than 5% of those in the field sample extracts, in most cases. The concentrations in the samples were blank-corrected.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To overcome the problem of coelution, chiral analysis of POPs is generally performed by heart-cut multidimensional gas chromatography (MDGC) [7,11,[15][16][17][19][20][21][22] and comprehensive two-dimensional gas chromatography (GC x GC) [11,15,17,19]. An excellent review of multidimensional chromatography in pesticides analysis can be found in Tuzimski [23].…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides are typically solvent extracted from soil by Soxhlet extraction [9,18,20,21,24,25] and by sonication [7]. Microlitre amounts are injected for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…24,26) Monitored ions are given in these references. Analytical methods for PCB atropisomers by other research groups [27][28][29][30][31][32] involve chromatography on chiral-phase columns with detection by electron impact MS. The most popular column is ChirasilDex (10% permethylated 2,3,6-tri-O-methyl β-cyclodextrin as chiral selector in polysiloxane, 25 or 30 m×0.25 mm i.d., 0.25 µm film, Chrompack or Varian), and in one case 29) Cyclosil-B (30% heptakis (2,3-di-O-methyl-6-Otert-butyldimethylsilyl)-β-cyclodextrin in 14% cyanopropylphenyl/86% methylpolysiloxane, 30 m×0.25 mm i.d., 0.5 µm film, Agilent, U.S.A.) was also used.…”
Section: Methodsmentioning
confidence: 99%